2020
DOI: 10.1038/s41598-020-67707-x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of semen quality among Chinese sperm donor candidates during the past 11 years

Abstract: Studies suggest that semen quality is declining globally, however, the debate remains open due to the possible effects of ethnic and geographical differences. This study aimed to explore whether semen quality of sperm donor candidates has changed in Henan Province, China from 2009 to 2019. In this retrospective study, we included 23,936 sperm donor candidates who were recruited by the Henan Human Sperm Bank of China between 2009 and 2019. To minimize intra-individual bias, we included only the first ejaculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…By contrast, a study from 2020 that assessed semen data from 23,936 sperm donor candidates at the Henan Sperm Bank of China between 2009 and 2019 did report temporal semen changes 138 . Using multiple linear regression analyses to account for potential confounders (age, BMI, sexual abstinence) suggested that sperm concentration decreased from 62 × 10 6 /ml in 2009 to 32 × 10 6 /ml in 2019 ( P < 0.001), with an average annual rate of 3.9%.…”
Section: Temporal Trends In Human Semen Qualitymentioning
confidence: 88%
See 2 more Smart Citations
“…By contrast, a study from 2020 that assessed semen data from 23,936 sperm donor candidates at the Henan Sperm Bank of China between 2009 and 2019 did report temporal semen changes 138 . Using multiple linear regression analyses to account for potential confounders (age, BMI, sexual abstinence) suggested that sperm concentration decreased from 62 × 10 6 /ml in 2009 to 32 × 10 6 /ml in 2019 ( P < 0.001), with an average annual rate of 3.9%.…”
Section: Temporal Trends In Human Semen Qualitymentioning
confidence: 88%
“…Overall, the studies with the most relevant design were those that were based on a standardized and controlled assessment of sperm production throughout the study period; relied on a relatively homogeneous group of men throughout the study; covered a sufficiently long period; had a sufficient cross-sectional sample size, in view of the wide distribution of human sperm production; and accounted for the main covariates known to modulate sperm characteristics. In total, and on the basis of these criteria considered together, six studies can be considered to provide relatively robust data on the trends reported: Zorn et al 113 in partners of women with tubal obstruction in Ljubljana (Slovenia), Auger et al 108 among fertile candidates for sperm donation in the Paris area (France) and the studies of Centola et al 87 in Boston (USA), Gyllenborg et al 47 in Copenhagen (Denmark), Shine et al 144 in New Zealand and Liu et al in Henan 138 (China), the latter four studies being carried out among unselected candidates for sperm donation with unknown fertility status (see Supplementary Table 2 ). Five of these six studies reported a decrease in sperm production (sperm concentration and/or sperm count) over time, covering overall the period 1973–2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This controversy continues to provoke interest and scientific discussion today, as in the last year four groups published articles examining the question of SCs with two groups finding evidence for decline and two showing no decline (36)(37)(38)(39). The abundance of conflicting data on the topic continues to makes this debate controversial.…”
Section: What Is the Best Way To Account For Variations In Semen Quality Between Populations?mentioning
confidence: 99%
“…The study of semen quality is the most important and most commonly used clinical laboratory test to evaluate the capacity of male fertility. In 2010, the World Health Organization (WHO) guidelines lowered the sperm concentration reference interval from 20 million to 15 million/ml [10]. Osmolality is known as a solution's concentration of osmotically active particles.…”
Section: Introductionmentioning
confidence: 99%